1970
DOI: 10.3329/bjsir.v42i3.671
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Cadmium from Soil to Vegetable Crops

Abstract: A pot experiment was conducted in order to study the transfer of Cd from soil to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…OM in soil prevents the release of metals due to the formation of Metal-OM complex. This was in agreement with the findings of [18] who opined that OM content and other soluble compounds in soil influences the transfer of metals from soil to plants. As the amount of OM increases, there is atendency for more metals to be absorbed on the soilcomplex and hence reduce their mobility [19].The least amount of Cr recorded at station III may be due to higher association of the metal with residual non-extractable fractions which makes the metal less available.…”
Section: Metals Tf In Cabbagesupporting
confidence: 93%
“…OM in soil prevents the release of metals due to the formation of Metal-OM complex. This was in agreement with the findings of [18] who opined that OM content and other soluble compounds in soil influences the transfer of metals from soil to plants. As the amount of OM increases, there is atendency for more metals to be absorbed on the soilcomplex and hence reduce their mobility [19].The least amount of Cr recorded at station III may be due to higher association of the metal with residual non-extractable fractions which makes the metal less available.…”
Section: Metals Tf In Cabbagesupporting
confidence: 93%
“…1). The same results were reported by Hossain et al (2007). They showed that application of 5 mg Cd kg -1 soil decreased SDW and root dry weight (RDW) of lal sak and data sak plants while those of lettuce and spinach increased.…”
Section: Shoot/root Dry Weightssupporting
confidence: 88%
“…Used metal fittings, rubber, plastics, tires, paints, etc. are materials emitting Cd to the (Hossain et al 2007;Islam et al 2014a). Soil samples from the vicinity of textile industries in Bangladesh have been reported (Kashem and Singh 1999) to contain mean concentration of 56.4, 51.1, and 164 mg/kg of Pb, Ni, and Cd, respectively.…”
Section: Metal Contamination In Soilmentioning
confidence: 96%